Electrochemical Characterization of Current‐Producing Human Oral Pathogens by Whole‐Cell Electrochemistry. Issue 9 (11th March 2020) - Naradasu, Divya; Guionet, Alexis; Okinaga, Toshinori; Nishihara, Tatsuji; Okamoto, Akihiro
Abstract: Extracellular electron transfer (EET) via cell‐bound redox enzymes and/or redox shuttles is extensively studied in environmental bacteria. Meanwhile, EET capable pathogens have been identified in the human gut. However, other EET‐capable bacterial niches where possible biofilm infections are prominent have scarcely been explored. Herein, we electrochemically characterized human oral biofilm pathogens, Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis, to examine their EET capability. Both strains showed current production with the electrode poised at +0.4 V vs. a standard hydrogen electrode, which was associated with a decrease in electron‐donor concentration, coupled with the appearance of oxidative peaks in differential pulse (DP) and cyclic voltammograms (CV). Addition of antibiotics that suppress the biosynthesis of membrane or protein showed a significant current decrease, demonstrating that current production reflects the cellular activity in these pathogens. DPV‐ and CV‐based kinetic analyses supported by transmission electron microscopy of the cells stained for transition metals suggest a potential EET mechanism associated with the presence of redox enzymes on the cell membrane. These results could be the basis to reevaluate human oral pathogens from an electroactive point of view. The identified electrochemical activity of the two strains can be an effective test for assessing the impact of antibacterial compounds on the pathogen cellular activity on an electrode. Abstract : Open wide : Current production capability, in Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis, is characterized through electrochemical analyses by using single potential amperometry and voltammetric analysis, and is associated with the lactate and glucose metabolism.